Case report: Coronary atherosclerosis in a patient with long-standing very low LDL-C without lipid-lowering therapy - Giorgio Mottola; Francine K. Welty; Hamid R. Mojibian; Kamil F. Faridi (Frontiers in Cardiovascular Medicine, 2023)
BackgroundApoB-containing lipoproteins including low-density lipoprotein cholesterol (LDL-C) are necessary for the development of atherosclerosis, and lifelong exposure to low serum levels of LDL-C have been associated with a substantial reduction of cardiovascular risk. Although plaque regression has been observed in patients with serum LDL-C less than 70–80 mg/dl on lipid-lowering therapy, an LDL-C level under which atherosclerosis cannot develop has not been established.Case presentationIn this case we describe a 60-year-old man with well-controlled diabetes mellitus and hypertension who presented to the hospital after an acute stroke likely due to an atrial myxoma discovered on imaging. A coronary computed tomography angiography scan performed in preparation for the planned surgical myxoma resection revealed an anomalous origin of the right coronary artery as well as evidence of nonobstructive coronary atherosclerosis in the right coronary and non-anomalous left coronary system. Despite not having ever been on any lipid-lowering therapy, this patient was found to have low LDL-C levels (<40 mg/dl) during this admission and on routine laboratory data collected over the prior 16 years. His family history strongly suggested heterozygous familial hypobetalipoproteinemia as a possible diagnosis.ConclusionsThis case illustrates that even long-standing, very low levels of LDL-C may be insufficient to completely prevent atherosclerosis and emphasizes the importance of primordial prevention of all cardiovascular risk factors.